Pengaruh Kebahagiaan di Tempat Kerja terhadap Kinerja Karyawan di PT Yupi Bogor - Ratinia Sarani (Arus Jurnal Pendidikan, 2023)
This research was conducted to see whether the effect of happiness at work on the performance of employees at PT. Yupi Bogor. The variable Happiness at Work is measured by the Happiness at Work (HAW) scale compiled by Fisher (2010) based on the aspects of happiness at work put forward by Fisher (2010), namely job satisfaction, organizational commitment), and work engagement. and Employee Performance is measured by the employee performance scale compiled by Mathis and Jackson (2006) based on the aspects of employee performance put forward by Mathis and Jackson (2006), namely quantity, quality, punctuality, absence and ability to cooperate. This research involved 95 employees of PT. Yupi Bogor using a non-probability sampling technique with a purposive sampling technique, then analyzing the data using simple linear regression using the SPSS application version 20.0 for Windows. The results showed that there was a positive and significant effect of happiness at work on employee performance with a contribution of 50.1% of happiness at work on employee performance